2013
DOI: 10.1017/s0021932013000060
|View full text |Cite
|
Sign up to set email alerts
|

Adult Anthropometric Measures and Socio-Demographic Factors Influencing Age at Menarche of University Students in Malaysia

Abstract: Early onset of menarche has been shown to be associated with breast cancer and ischaemic heart disease. Studies on age at menarche of the Malaysian population are poorly documented. This study aimed to determine the influence of anthropometric and socio-demographic factors on the age at menarche of university students in Malaysia. Data were obtained in 2010-11 from 961 students between the ages of 18 and 25 years from the University of Malaya using stratified sampling, and multiple regression analysis was appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 41 publications
3
2
0
Order By: Relevance
“…The median age at menarche in this study is lower than that found in a previous study on Filipino girls aged 14-15 years (Adair, 2001), which found it to be 13.1 years, with 50% of girls attaining menarche between the ages of 12.4 and 13.9 years. This study's estimated median age at menarche for Filipino women, ranging between 12.6 years for the 1973-1977 birth cohort and 12.3 years in the 1993-1997 birth cohort, is rather close to that of other Asian populations: 12.0 years in Malaysia (Hossain et al, 2013), 12.5 years in Thailand, 12.4 years in Hong Kong, 12.6 years in Japan and 12.1 years in India (Parent et al, 2003). Across the birth cohorts, the mean age at menarche was about 0.6-0.7 years higher than the median, indicating that the data are positively skewed, as few women had their menstruation at ages 16 and above.…”
Section: Discussionsupporting
confidence: 54%
“…The median age at menarche in this study is lower than that found in a previous study on Filipino girls aged 14-15 years (Adair, 2001), which found it to be 13.1 years, with 50% of girls attaining menarche between the ages of 12.4 and 13.9 years. This study's estimated median age at menarche for Filipino women, ranging between 12.6 years for the 1973-1977 birth cohort and 12.3 years in the 1993-1997 birth cohort, is rather close to that of other Asian populations: 12.0 years in Malaysia (Hossain et al, 2013), 12.5 years in Thailand, 12.4 years in Hong Kong, 12.6 years in Japan and 12.1 years in India (Parent et al, 2003). Across the birth cohorts, the mean age at menarche was about 0.6-0.7 years higher than the median, indicating that the data are positively skewed, as few women had their menstruation at ages 16 and above.…”
Section: Discussionsupporting
confidence: 54%
“…But some other studies showed a significant rural urban variation [36]. Students from small-sized families attained menarche earlier than those from larger families (F=4.106; P<0.05), similar result was found in Malaysian girls [36].…”
Section: Discussionsupporting
confidence: 62%
“…In the previous studies conducted at different countries reported that the AAM is lower among the girls of Mexico [30], France [31] and higher among the girls of Brazil [32], Korea [33], Uganda [34], Ethiopia, [35], Malaysia [36], Kuwait [37], Jordan [38], Nigeria [39], Bangladesh [40], China [41] and Indonesia [42] (Fig. 3).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Students from small-sized families attained menarche earlier than those from larger families [24]. The results of this study (Table 2)also reveal that the mean menarcheal age is found relatively the lowest (11.67 years) among the respondents whose family members are less than or equal to four.…”
Section: Resultssupporting
confidence: 54%